Embryonic Development in Arabidopsis Thaliana: From the Zygote Division to the Shoot Meristem - Boscá, Sonia; Knauer, Steffen; Laux, Thomas (Frontiers in Plant Science, 2011)
Postembryonic organ formation of plants is fueled with cells from the stem cell niches in the shoot and root meristems. During the last two decades many players that regulate stem cell maintenance have been identified. With these factors in hand, the mechanisms establishing stem cell niches during embryo development can be addressed. Here we discuss current models of how the shoot meristem stem cell niche arises during Arabidopsis embryo pattern formation.